Cold-active enzymes in the dairy industry: Insight into cold adaption mechanisms and their applications. (July 2022) - Chen, Qiuming; Wu, Yanchang; Huang, Zhaolin; Zhang, Wenli; Chen, Jie; Mu, Wanmeng
Abstract: Background: With a growing desire for low-cost and energy-saving alternatives to the use of harsh chemicals in industrial processes, as well as a growing environmental concern, cold-active enzyme (CAE) has caught the interest of scientists all over the world. It shows great potential for applications in a variety of industries, including the dairy industry. Scope and approach: This work aimed to present a comprehensive overview of the biochemical features of cold-active enzymes and the origin of their cold adaptations, with a specific focus on the applications in the dairy industry. Key findings and conclusions: We described the unique adaptive features of CAEs from aspects of thermostability and catalytic rate, along with a discussion of the computational methods used to investigate the underlying molecular basis of enzyme adaptation to low temperatures. Finally, the roles of some CAEs explored so far in the dairy industry, including β -galactosidase, cellobiose 2-epimerase, transglutaminase, and proteases, and their applications were described. The review highlights the significance of developing CAEs and the prospects for their applications in the dairy industry. Highlights: Cold-active enzyme (CAE) maintains high catalytic activity at low temperatures. CAE shows great potential in industrial applications due to its cost-effectiveness. CAE compromises between conformational rigidity and catalytic efficiency. Computational methods are used to uncover the principles behind cold adaptation. CAEs can be exploited for various applications in the dairy industry.